Pathogenesis mechanisms employed by Alternaria species (Journal of Oilseed Brassica, 2026)
Alternaria species are mainly saprophytic fungi, but some have acquired pathogenic capacities causing plant diseases over a broad host range. More than 70 phytotoxins are produced by them from which only a small proportion have been chemically characterized and reported to act as mycotoxins. Host-selective toxins (HSTs) produced by Alternaria plant pathogens are generally low-molecular-weight secondary metabolites with a diverse range of structures that function as effectors controlling pathogenicity or virulence in certain plant–pathogen interactions. This review summarizes all the diseases caused by Alternaria spp., mycotoxins produced by Alternaria spp. and the recent advances in elucidating mode of action of host specific Alternaria toxins at physiological, biochemical and molecular levels